Photocatalytic efficacy of ZnO films – light intensity and thickness effects. (3rd July 2017) - Ravichandran, K.; Sindhuja, E.; Uma, R.; Arun, T.
ABSTRACT: The aim of this work is to investigate the effects of film thickness, light intensity and Ag incorporation on the photoctalytic efficacy of zinc oxide films. ZnO films with different thicknesses were prepared using an automated home-made jet nebuliser spray technique. The results show that the thickness of the film has no appreciable influence on the photocatalytic efficiency of ZnO films whereas the light intensity strongly influences the photocatalytic activity of ZnO films. It is also found that doping of Ag with ZnO causes considerable enhancement in the photocatalytic activity. The dye degradation rate constant in the case of undoped ZnO film with thickness 400 nm is 0.0263min-1, whereas for Ag doped ZnO film having the same thickness, it is 0.0530 min −1 . The reason for this enhancement in the photocatalytic efficacy of ZnO:Ag film is addressed with the help of optical band gap and the reported characteristics of Ag.